Perilaku Prososial Pada Anak Yang Menjalani Program Full Day Dan Reguler Di Kabupaten Sleman - Siti Maimunah; Gunarmi (Nan Tongga Health And Nursing, 2025)
Children as the next generation and future managers of the nation need to be prepared from an early age through the fulfillment of their rights, namely the right to live, grow, develop, and participate fairly in accordance with human dignity and dignity, and receive protection from violence and discrimination. As mandated in Law No. 23 of 2002 concerning Child Protection, guaranteeing and fulfilling children's rights is a shared responsibility of parents, families, communities, and the State. The target of the Sustainable Development Goals (SDGs), namely quality education by 2030, ensures that all girls and boys have access to quality early childhood development, care, and pre-primary education. Preschool education providers such as kindergartens are the most important agents that replace the role of parents in care and education. This study aims to determine the differences in prosocial behavior in children who undergo full-day and regular programs. This type of research is quantitative research with a cross-sectional time approach. This study used 68 respondents aged 4-6 years who were divided into two groups. The group of respondents who participated in the full-day program consisted of 34 children and the group of respondents who participated in the regular program consisted of 34 children. The sampling technique used proportional simple random sampling, and the examination used a prosocial behavior observation sheet. Data analysis used Mann-Whitney and Ordinal Logistic Regression. The results showed that prosocial behavior in children who participated in the full-day program was better than children who participated in the regular program (p-value prosocial behavior = 0.02).